Elite Puri dalam Lanskap Politik Kontemporer di Bali - I Putu Gede Suwitha (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
There is been few studies on the role of local or traditionalelites in Bali in the context of national politics in Bali. It seemsthat the traditional Balinese elites played a dominant role inthe context of political culture in the past, particularly sincethe fall of Bali in the fourteenth Century until nineteenthcentury. However, this situation has still developed inthe recent situation and will be in the future. This studyconcentrates on the role of the traditional Balinese elites inthe context of recent situation in terms of democracy and theinvolvement of the elites particularly after the reformationperiod and also trying to show to what extent the role of thetraditional Balinese elite in terms of democracy in modernpolitics.